2014
DOI: 10.1017/s0950268814002386
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and incidence of tuberculosis infection conversion in contacts of pulmonary tuberculosis patients: a prospective cohort study

Abstract: The objective of this study was to estimate the relationship between serum vitamin D (VitD) status and tuberculosis (TB) infection conversion (TBIC), measured by the tuberculin skin test (TST) and an interferon-gamma release assay, the QuantiFERON-TB Gold In-Tube (QFT-GIT) test, in the contacts of pulmonary TB patients in Castellon (Spain) in a prospective cohort study from 2010 to 2012. Initially, the participants were negative to latent TB infection after a screening that included TST and QFT-GIT tests, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 37 publications
(43 reference statements)
0
33
1
Order By: Relevance
“…Twelve articles were selected for qualitative review, including 1 cohort study and 12 cross-sectional studies (1 article contained a cross-sectional study and a cohort study [22]; Figure 1). The characteristics of the 13 included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve articles were selected for qualitative review, including 1 cohort study and 12 cross-sectional studies (1 article contained a cross-sectional study and a cohort study [22]; Figure 1). The characteristics of the 13 included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…4850 Our analysis using a fixed-effect model revealed significant association between VDD and an increased risk of TST conversion/TBIC (OR =3.99; 95% CI =[1.88, 8.45]; P =0.0003; I 2 =0) (Figure 3C). …”
Section: Resultsmentioning
confidence: 88%
“…Multiple risk factors may determine the outcome of exposure, including two interesting recently implicated factors, Vitamin D levels and host genetics. Sufficient Vitamin D levels may be a protective factor for Mtb infection [27]. Genome-wide association studies in a South African cohort revealed a genetic locus associated with persistent TST negativity in an endemic area [25].…”
Section: Session 1: Prevention Of Sustained Infection Withmentioning
confidence: 98%